Salt, Aldosterone, and Parathyroid Hormone: What Is the Relevance for Organ Damage?. (19th September 2017) - Catena, Cristiana; Colussi, Gian Luca; Brosolo, Gabriele; Bertin, Nicole; Novello, Marileda; Palomba, Andrea; Sechi, Leonardo A.
Abstract : Structured interventions on lifestyle have been suggested as a cost-effective strategy for prevention of cardiovascular disease. Epidemiologic studies demonstrate that dietary salt restriction effectively decreases blood pressure, but its influence on cardiovascular morbidity and mortality is still under debate. Evidence gathered from studies conducted in patients with primary aldosteronism, essential hypertension, or heart failure demonstrates that long-term exposure to elevated aldosterone results in cardiac structural and functional changes that are independent of blood pressure. Animal experiments and initial clinical studies indicate that aldosterone damages the heart only in the context of an inappropriately elevated salt status. Recent evidence suggests that aldosterone might functionally interact with the parathyroid hormone and thereby affect calcium homeostasis with important sequelae for bone mineral density and strength. The interaction between aldosterone and parathyroid hormone might have implications also for the heart. Elevated dietary salt is associated on the one hand with increased urinary calcium excretion and, on the other hand, could facilitate the interaction between aldosterone and parathyroid hormone at the cellular level. This review summarizes the evidence supporting the contribution of salt and aldosterone to cardiovascular disease and the possible cardiac and skeletal consequences of the mutual interplay between aldosterone, parathyroid hormone, and salt.